Consensus guidelines for the safe prescription and administration of oral bowel-cleansing agents. Issue 11 (26th July 2012) - Connor, Andrew; Tolan, Damian; Hughes, Stephen; Carr, Nick; Tomson, Charles
Abstract : Oral bowel-cleansing preparations are used before colonic surgery and endoscopic and radiological assessment of the intestine to minimise faecal contamination. In February 2009, the UK National Patient Safety Agency issued a Rapid Response Report highlighting the potential risk of harm associated with the use of these preparations and instructing local NHS Trusts to implement safeguards to reduce this risk. This guidance has been prepared to help NHS Trusts to respond to these concerns, as the risk of complications is influenced by both individual patient risk factors and the choice of bowel preparation, for which definitive guidance was not previously available. This document provides an outline of the different available oral bowel-cleansing agents and the complications that may arise. This is followed by recommendations for their use in different patient groups and circumstances. The recommendations are based on consensus between the authors, each of whom circulated drafts to members of their specialist society. The evidence for these recommendations has been assessed using the modified GRADE system. The recommendations cover the choice, administration and complications (relative and absolute) of the different oral bowel-cleansing agents, with specific guidance provided for different patient groups.